FINANCIAL ANXIETY AND FINANCIAL MANAGEMENT BEHAVIOR AMONG PUBLIC EMPLOYEES: THE MEDIATING ROLE OF FINANCIAL SELF-EFFICACY - Iwan Sariono Sukadi; Felisitas Defung; Wirasmi Wardhani (CV. Radja Publika, 2026)
Financial management behavior has become a critical concern in the global behavioral finance literature because financial anxiety increasingly affects household decision-making, employee well-being, and workplace functioning. Although previous studies consistently acknowledge the negative role of financial anxiety, the psychological mechanisms explaining how such anxiety translates into actual financial behavior among public employees remain underexplored. This study aims to examine the effect of financial anxiety on financial management behavior among civil servants in Balikpapan City, with financial self-efficacy tested as a mediating mechanism. Using a quantitative explanatory design, data were collected from 364 civil servants and analyzed through PLS-SEM with SmartPLS. The findings reveal that financial anxiety directly weakens financial management behavior and indirectly reduces it through lower financial self-efficacy, while financial self-efficacy emerges as the strongest predictor of positive financial behavior. This study contributes theoretically by extending social cognitive theory into the public sector financial behavior context and offers practical implications for employee financial wellness interventions. The explicit novelty lies in demonstrating financial self-efficacy as the central psychological bridge linking financial anxiety to civil servants' financial management behavior.